Safety and efficacy of transvenous lead extraction in octogenarians using powered extraction sheaths. Issue 4 (26th February 2021) - Burger, Heiko; Hakmi, Samer; Petersen, Johannes; Yildirim, Yalin; Choi, Yeong‐Hoon; Willems, Stephan; Reichenspurner, Hermann; Ziegelhoeffer, Tibor; Pecha, Simon
Abstract: Background: In the aging population equipped with cardiac implantable electronic devices, an increasing number of octogenarians require lead extractions. This patient population is often considered as a high‐risk group for surgical procedures. We, therefore, investigated the safety and efficacy of transvenous lead extraction in octogenarians using powered extraction sheaths. Methods: Between January 2013 and March 2017, 403 patients underwent lead extraction at two high‐volume lead extraction centers. A total of 71 octogenarians were treated with laser lead extraction and were included in this analysis. Primary extraction method was laser lead extraction, with additional use of mechanical rotational sheaths or femoral snares, if necessary. Patient‐based and procedural data were collected and analyzed retrospectively. Results: Mean age was 83.5 ± 3.3 years, 64.7% were males. A total of 152 leads were extracted. The mean lead dwell time of treated leads was 10.2 ± 5.2 years. Complete procedural success rate was 92.9%, while clinical success was achieved in 98.6%. Failure of extraction occurred in one patient (1.4%). In six (7.7%) patients, additional mechanical rotational sheaths or femoral snares were used. Overall complication rate was 4.2%, including one (1.4%) major (RA perforation) and two (2.8%) minor complications. No procedure‐related mortality was observed in any of the patients. Conclusion: Transvenous lead extraction in octogenarians with old leads is safe and effective when performed in experienced centers. Patient's age should therefore not be considered as contraindication for lead extraction using powered extraction sheaths.